Evaluation of the Candida sp. 99-125 Lipase Positional Selectivity for 1, 3-Diolein Synthesis. (20th May 2019) - Bi, Yanhong; Duan, Zhangqun; Zhang, Wenjing; Xu, Lei; Wang, Zhaoyu; Zhao, Xiaojuan; Zhao, Xiangjie; Yang, Jiali
Abstract : In this study, comparative experiments were carried out to investigate the positional selectivity of Candida sp. 99–125 lipase in preparing 1, 3-diolein by using medium engineering strategy. The results indicated that the diolein yield was markedly enhanced from 56.5% to 86.7% with increasinglog ⁡ P values of the solvents, while the selectivity of the examined lipase for the sn-1 over the sn-2 hydroxyl of glycerol was decreased, thus leading to a reduced 1, 3-diolein to 1, 2-diolein ratio. To evaluate the possibility of industrial enzymatic production of 1, 3-diolein, larger-scale experiments were assessed. After being used repeatedly for eight batches, the diolein content reached 95.1%, while the 1, 3-diolein to 1, 2-diolein ratio was 7:1 following purification. Results of the kg level experiments significantly demonstrated the practicability of the enzymatic process and the efficiency of the purification strategy for the product.